Managerial accounting : concepts for planning, control, decision making - Garrison, Ray H (Irwin HomewoodUS, 1993)
Focuses on internal uses of accounting data by managers in directing the affairs of business and nonbusiness organizations. Looks at topics such as cost terms; cost behaviour; systems design; planning and control; and, using cost data in decision making.